Ataxia-televangelist mutated (ATM)/ ATR serine/threonine kinase (ATR)-mediated RAD51 recombinase (RAD51) promotes osteogenic differentiation and inhibits osteoclastogenesis in osteoporosis. Issue 2 (1st February 2022) - Qiu, Minli; Tu, Liudan; Zhao, Minjing; Yang, Mingcan; Qi, Jun; Xie, Ya; Gu, Jieruo
ABSTRACT: Osteoporosis is a metabolic bone disease that significantly affects the quality of life and can even lead to death. In this study, we aimed to investigate the role of RAD51 recombinase (RAD51) in osteoblast and osteoclast differentiation. We analyzed differentially expressed genes using microarray analysis. The osteogenic differentiation capability was analyzed by alkaline phosphatase (ALP) staining and alizarin red staining assays. Osteogenesis and osteoclast related genes expression was detected using quantitative real-time PCR (qPCR) and Western blotting. The phosphorylation of Ataxia-telangiectasia mutated (ATM) and ATR serine/threonine kinase (ATR) was tested using Western blotting. The effect of RAD51 on osteoporosis was also explored in vivo. The results showed that RAD51 was downregulated in osteoporosis, but upregulated in differentiated osteoblasts. Overexpression of RAD51 enhanced the differentiation of osteoblasts and suppressed the formation of osteoclasts. Furthermore, p-ATM and p-ATR levels were upregulated in osteoblasts and downregulated in osteoclasts. RAD51 expression was reduced by the ATM/ATR pathway inhibitor AZ20. AZ20 treatment inhibited osteoblastogenesis and promoted osteoclastogenesis, whereas RAD51 reversed the effects induced by AZ20. Moreover, RAD51 improved bone microarchitecture in vivo. Taken together, ATM/ATR signaling-mediated RAD51 promoted osteogenic differentiation and suppressed osteoclastogenesis. These findings reveal a critical role for RAD51 in osteoporosis.